2018
DOI: 10.1093/icb/icy018
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Organismal Biology to Forecast the Effects of Climate Change

Abstract: Despite the pressing need for accurate forecasts of ecological and evolutionary responses to environmental change, commonly used modeling approaches exhibit mixed performance because they omit many important aspects of how organisms respond to spatially and temporally variable environments. Integrating models based on organismal phenotypes at the physiological, performance, and fitness levels can improve model performance. We summarize current limitations of environmental data and models and discuss potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 87 publications
0
22
0
Order By: Relevance
“…This inaccurate mapping of actual exposure temperatures at the local scale may compromise our ability to project vulnerability assessments to ongoing global climatic predictions (Sunday et al., ). For instance, coarse‐resolution climatic layers may overestimate risk to suffer heat impacts as estimated thermal regimens exceed species upper thermal tolerances (Buckley, Cannistra, & John, ; Storlie et al., ). Our results revealed that the probability to suffer acute heat impacts was similar across elevations and habitats.…”
Section: Discussionmentioning
confidence: 99%
“…This inaccurate mapping of actual exposure temperatures at the local scale may compromise our ability to project vulnerability assessments to ongoing global climatic predictions (Sunday et al., ). For instance, coarse‐resolution climatic layers may overestimate risk to suffer heat impacts as estimated thermal regimens exceed species upper thermal tolerances (Buckley, Cannistra, & John, ; Storlie et al., ). Our results revealed that the probability to suffer acute heat impacts was similar across elevations and habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Translating environmental conditions into organismal performance is one of the significant challenges when interpreting ecological responses to changes in the environment [75]. Temperature is widely studied given the pervasive effect of temperature on virtually all biological systems [76].…”
Section: Synergic Effects Of Water Balance and Body Temperature On Bementioning
confidence: 99%
“…Mechanistic models, in contrast, do not require extrapolation, because they directly integrate species’ functional traits with available microclimates. Thus, mechanistic models theoretically provide a solid basis with which to predict species’ distributions in changing climates (Buckley, Cannistra, & John, ; Buckley et al, ; Kearney & Porter, ; Sears, Raskin, & Angilletta, ). Furthermore, mechanistic models can offer invaluable insights into the proximate constraints that underpin species’ range limits (Kearney & Porter, ).…”
Section: Introductionmentioning
confidence: 99%